Presence of Escherichia coli O157 in young alpacas (Vicugna pacos) - Silvera C., Elvis (2012)
The study aimed to evaluate the presence of E. coli O157 (rfb O157 gene) in young alpacas (Vicugna pacos) with and without diarrhea, and the genes that codify their main factors of virulence such as intimin (eae gene), Shiga toxin 1 (gene Stx1) and Shiga toxin 2 (Stx2 gene). Strains of E. coli from a previous study in Puno, Peru were used. A total of 55 and 52 strains of E. coli from young alpacas with and without diarrhea respectively were used. Strains were processed by the polymerase chain reaction (PCR) technique. Both groups resulted negative for the presence of E. coli O157. In the group of alpacas without diarrhea, 7 strains were positive for the gene eae and 4 for Stx2. In the group of alpacas with diarrhea 2 strains were positive for the genes eae and Stx1, 1 for eae and Stx2, 5 for eae, 1 for Stx1 and 5 for Stx2. The survey did not identify the presence of serogroup E. coli O157; however identified the presence of Stx and eae genes which shows that this species might be acting as domestic reservoir of enterohaemorrhagic E. coli.